Implementasi Program Kerja PMT Eco Print di SDN 4 Sidodadi Kecamatan Ngantang Kabupaten Malang: Peningkatan Kesadaran Lingkungan Melalui Kreativitas Siswa - Muhammad Fauzi Emqi; Junershy Liensi Magana; Crisdayanti Uceng; Stefania Hoar Nahak; Evaristus Aldin; Marselina Mura; Inosensia Taek; Yuliana Belak; Maria Juita Sarina (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
This article discusses the implementation of the PMT (Integrated Internship Program) Eco print program at SDN 4 Sidodadi, Ngantang District, Malang Regency. The purpose of this program is to increase students' environmental awareness through the introduction of eco print techniques on fabric media as a form of creativity based on the utilization of natural materials. This program also aims to introduce environmentally friendly concepts from an early age and hone students' skills in creating artworks. Through a direct practice approach, it is expected that students can understand the importance of environmental conservation and foster a love for nature.